1881 Ind. Rev. Stat. 371 - (:unkn) unknown (My University, 1881)
§ 1984: Prohibited brandishing any pistol, dirk, knife, slung-shot, or any other deadly or dangerous weapon. Violators fined any sum not less than one nor more than five hundred dollars.
Keywords: BRANDISHING